Diffuse Presence of Myeloblasts in Chronic Subdural Hematoma of a Young Adult Patient without Systemic Hematologic Disorder - Yokoyama, Shota; Fukuhara, Toru; Namba, Yoichiro; Asakura, Shoji (Journal of Neurological Surgery Reports, 2014)
Objective Myeloblasts are rarely found in the composition of a chronic subdural hematoma (CSH), and reported cases with myeloblasts in CSH have all been associated with systemic hematologic disorders. We present a young man with CSH manifesting the diffuse presence of myeloblasts, although no systemic hematologic disorders were identified.Participant A 27-year-old man, complaining of a headache lasting for a few months, was diagnosed with right CSH, and the aspirated hematoma was sent for cytological evaluation because no apparent etiologic episode was found. The diffuse presence of precursor cells, such as myeloblasts and erythroblasts, mimicking the aspirated bone marrow, was confirmed. This finding was suggestive of a systemic hematologic disorder, although the systemic evaluations were negative.Results The patient's hematoma reaccumulated twice, and finally hematoma and enhanced dura were removed by craniotomy under general anesthesia. Further histologic evaluation did not show any precursor cells, and he has remained asymptomatic for > 2 years without any evidence of the hematologic disorder.Conclusion We believe this is the first case with CSH that contained myeloblasts as well as erythroblasts in an otherwise healthy patient. A possible etiology was considered for the origin of precursor cells in his CSH.
Keywords: chronic subdural hematoma; erythroblast; hematologic disorder; myeloblast